Laksa Gurih web application in strengthening surveillance and assistance for malnourished children in Tangerang City - Amir, Chindy; Fitri, Yuni Pradilla; Arjuna, Tony (BKM Public Health and Community Medicine, 2021)
Objective: e-Laksa Gurih is present as an innovation of the Tangerang City Health Office in reducing malnutrition rates. This application innovation is related to strengthening the mentoring and surveillance of malnutrition in the City of Tangerang. Content: Laksa Gurih is a program to overcome malnutrition in the City of Tangerang. The Tangerang City Health Office developed the book into a web-based application starting as a pocketbook for Laksa Gurih cadres. The Health Office cooperated with the Tangerang City Communications and Information Office to make applications targetting the Health Office, nutritionists at the puskesmas, and cadres to accompany malnourished children in Tangerang City. It has been introduced to cadres through a training program for managing malnutrition at the Health Office. Its web application contains a dashboard for the development of malnutrition data, daily data entry for malnourished children, cohort reports, and readable and downloadable reference guidebooks. One companion cadre accompanies one malnourished child. They make home visits to toddlers every day and record the results of these visits into the e-Laksa Gurih application, which are weight, height, upper arm circumference, children's eating diaries, children's activities, other children's activities, and children's conditions. The cadres are very enthusiastic about the application because it makes it easier for them to assist and record during monitoring of malnourished children. The advantages are that monitoring and condition of malnourished children are known faster, more accurately, and more precisely. Health center nutritionists and the Tangerang City Health Office no longer wait for the end of the month to get data on malnourished children to take the next step quickly. The drawback of this application is that access to Laksa Gurih via cellphone is still too complicated, so further development is needed. Objective: e-Laksa Gurih hadir sebagai inovasi Dinas Kesehatan Kota Tangerang dalam menurunkan angka gizi buruk. Inovasi aplikasi ini berkaitan dengan penguatan pendampingan dan surveilans gizi buruk di Kota Tangerang. Content: Laksa gurih merupakan sebuah program penanggulangan gizi buruk di Kota Tangerang. Berawal dari sebuah buku saku kader pendamping laksa gurih, Dinas Kesehatan Kota Tangerang mengembangkan buku tersebut menjadi sebuah aplikasi webbased. Dinas Kesehatan bekerjasama dengan Dinas Kominfo Kota Tangerang dalam pembuatan aplikasi. Sasaran pengguna aplikasi ini yaitu Dinas Kesehatan, ahli gizi puskesmas dan kader pendamping anak gizi buruk di Kota Tangerang. Aplikasi web Laksa Gurih berisi dashboard perkembangan data gizi buruk, entry data harian anak gizi buruk, laporan kohort dan referensi buku-buku panduan yang bisa dibaca serta di download. Satu anak gizi buruk didampingi satu orang kader pendamping. Kader pendamping melakukan kunjungan rumah balita setiap hari dan mencatat hasil kunjungan tersebut kedalam aplikasi e-Laksa Gurih. Data yang harus diinput kader kedalam aplikasi tersebut berupa berat badan, tinggi badan, LLA, catatan harian makan anak, kegiatan anak, kegiatan lain anak dan kondisi anak. Aplikasi ini sudah diperkenalkan kepada kader-kader melalui acara pelatihan tatalaksana gizi buruk di Dinas Kesehatan Kota Tangerang. Para kader sangat antusias terhadap aplikasi tersebut karena memudahkan mereka dalam pendampingan dan pencatatan selama pemantauan anak gizi buruk. Kelebihan aplikasi ini yaitu pemantauan dan keadaan anak gizi buruk lebih cepat diketahui, lebih akurat dan lebih spesifik. Ahli gizi puskesmas dan Dinas Kesehatan Kota Tangerang tidak lagi menunggu akhir bulan untuk mendapatkan data anak gizi buruk sehingga bisa dengan cepat mengambil langkah selanjutnya. Kekurangan aplikasi ini yaitu akses Laksa Gurih melalui handphone masih terlalu rumit, sehingga dibutuhkan pengembangan lebih lanjut.